Recycling of rice straw (Oryza sativa) and cow dung as compost with fungal activator (Rhizopus oryzae) and analysis of nutrient content by atomic absorption spectrophotometry (AAS) - Gunawan, Inriya; Sari, Mistia; Anwar, Hendra; Junialdi, Rezi (The Future of Education Journal, 2025)
The management of rice straw (Oryza sativa) waste in Indonesia, particularly in Pasaman Regency, faces significant challenges due to the widespread practice of open burning, which harms the environment and poses health risks to local communities. Despite this, rice straw holds great potential as an organic compost material that is environmentally friendly and nutrient-rich. This study explores the use of Rhizopus oryzae, a fermentation fungus capable of accelerating the decomposition of rice straw, as an efficient, economical, and sustainable waste management solution. Through fermentation, rice straw can be converted into high-quality compost that enhances soil fertility and agricultural productivity while reducing dependence on chemical fertilizers. This technology is highly relevant in promoting sustainable agriculture and climate change mitigation by lowering greenhouse gas emissions. However, field adoption still faces challenges, particularly in fermentation control and farmer outreach. Therefore, policy support, technical training, and cross-sector collaboration are essential to ensure broad and effective implementation. This approach presents a strategic solution for environmentally friendly agricultural waste management and improving farmer livelihoods in the future.